The Collected Works of Samuel Taylor Coleridge, Volume 9 : Aids to Reflection - Coleridge, Samuel Taylor; Beer, John B. (Princeton, NJ : Princeton University Press, 2017)
Coleridge's Aids to Reflection was written at a time when new movements in thought were starting to unsettle belief. It was read with admiration by early Victorians such as John Sterling, F. D. Maurice, and Thomas Arnold, contributing to the formation of the Broad Church Movement, and with respect by members of the High Church Movement, including John Henry Newman. Coleridge had intended simply to produce a selection from the writings of the seventeenth-century Archbishop Robert Leighton with comments of his own, but as he worked at the book he found the commentary expanding to take in the fruits of his religious thinking over the years, so that the second, and more important, part of the volume was totally dominated by his thought. In this, the first major edition of Aids to Reflection, the intricate story of Coleridge's changing conception is unfolded by way of an introduction and detailed notes, the surviving materials for the volume being printed in appendixes. The introduction also traces the subsequent influence of the work in England and America; further appendixes include James Marsh's influential preface to the first American edition, which is reproduced in full.Originally published in 1993.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Contents -- List of Illustrations -- Editor's Foreword: Plan of This Edition; Acknowledgments -- Editorial Practice, Symbols, and Abbreviations -- Chronological Table 1772-1834 -- Editor's Introduction -- To the Reader -- Preface -- Aids to Reflection -- Prudential Aphorisms -- Reflections -- Moral and Religious Aphorisms -- Elements of Religious Philosophy -- Aphorisms On Spiritual Religion -- Aphorisms On that Which is Indeed Spiritual Religion -- Conclusion -- Appendix -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: Literature; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh